Molluscan Shellfish Aquaculture and Production - Huiping Yang; Leslie N. Sturmer; Shirley Baker (EDIS)
Molluscan shellfish aquaculture provides high quality and high value seafood for human consumption, and shellfish provide environmentally beneficial ecosystem services, such as nutrient extraction and water filtration, to the environment in which they are grown. In the past five decades, global fisheries and aquaculture have grown steadily, and seafood consumption per capita has increased. Molluscan shellfish has traditionally been a major component of world aquaculture. Today, molluscs are cultured in 76 countries. This 8-page fact sheet describes molluscan shellfish aquaculture in the United States and worldwide and outlines molluscan shellfish aquaculture stages and methodologies. Written by Huiping Yang, Leslie N. Sturmer, and Shirley Baker, and published by the UF School of Forest, Fisheries, and Geomatics Sciences, January 2016.